2007
DOI: 10.1136/jnnp.2007.137190
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life in people with Parkinson's disease left untreated at diagnosis

Abstract: Given the lack of significant deterioration in the PDQ-39 in untreated patients, we believe a "wait and watch" strategy for the treatment of newly diagnosed PD remains a credible approach unless randomised trials prove otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
13
2
3
Order By: Relevance
“…A recent study has shown that symptomatic therapy will improve the QoL of these patients both in the short and long term, whereas delaying it is associated with a decline as the disease progresses 4. The discrepancy between the present and recent studies in terms of the effect of treatment3 4 may in some part reflect local issues and QoL, and the significant limitations of the Parkinson’s disease questionnaire (PDQ-39) in measuring this in early disease, as well as the substantial differences in the relative sizes of the populations analysed. The benefits of drug treatment always need to be offset against potential side effects, hence the need to individualise and correctly sequence treatment.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…A recent study has shown that symptomatic therapy will improve the QoL of these patients both in the short and long term, whereas delaying it is associated with a decline as the disease progresses 4. The discrepancy between the present and recent studies in terms of the effect of treatment3 4 may in some part reflect local issues and QoL, and the significant limitations of the Parkinson’s disease questionnaire (PDQ-39) in measuring this in early disease, as well as the substantial differences in the relative sizes of the populations analysed. The benefits of drug treatment always need to be offset against potential side effects, hence the need to individualise and correctly sequence treatment.…”
contrasting
confidence: 61%
“…The decision whether to begin treatment for PD, and what treatment to begin, is a decision that must be tailored to individual patient characteristics,2 a view supported by the data and conclusions of the paper by Asimakopoulos and colleagues3 in this issue of J Neurol Neurosurg Psychiatry (see page ) . However, what information is available to the physician and patient to help guide this process?…”
mentioning
confidence: 99%
“…Dabei zeigte sich, dass zu beiden Nachuntersuchungsterminen die unbehandelten Patienten eine signifi kant schlechtere Lebensqualität hatten als die mit einer Monotherapie (unterschiedliche Substanzen) behandelten Patienten. In einer sehr viel kleineren Studie [ 45 ] bei 40 Patienten konnten diese Befunde nicht voll bestätigt werden. Zwar hatte auch hier die behandelte Gruppe eine bessere Lebensqualität.…”
Section: Comt-hemmer ▼unclassified
“…La EP determina un deterioro de la calidad de vida de los pacientes, sobrecarga para los familiares y cuidadores y un aumento de la mortalidad de los afectados 1 . Aproximadamente 1 a 2% de la población mayor de 65 años sufre EP, cifra que se eleva a 3%-5% en aquellos mayores de 85 años 2 .…”
unclassified
“…Basados en datos internacionales se puede estimar que existen cerca de 40.000 pacientes con EP en Chile 3 . Conocer el número de personas afectadas por una enfermedad es importante para diseñar adecuadamente los cuidados y destinar los recursos económicos y humanos correspondientes 1,5 . Este estudio tiene como objetivo evaluar la tendencia de mortalidad por EP en Chile en un período de 10 años y valorar las variaciones geográficas de dicha mortalidad.…”
unclassified